Evaluasi Keberhasilan Penggunaan Dana Desa (Studi Kasus Desa Maju Jaya Kecamatan Pelepat Ilir, Kabupaten Bungo) - Deka Veronica; Etik Winarni; ahmad Soleh (Universitas Batanghari, 2020)
Law No. 32 of 2004 on Villages that gives villagers the opportunity to organize and take care of their own households, which is organized by promoting the principles of democracy, participatory, equalization, justice and paying attention to the potential diversity of the region is the starting point of the development change from the periphery. And strengthened by government policy in 2015 the government issued the Village Fund policy, which was marked by the publication of PMK No.49 in 2016. The reforms are a form of seriousness from the government in trying to build the country through the village. But the goodwill is certainly not all can run in accordance with expectations given the competency conditions of human resources and various conditions. Therefore, in this study will evaluate the success of the use of village funds that have been given by the government, whether it has a positive impact on the community economy. This research will be conducted in Pelepat Ilir sub-district with case studies in Maju Jaya Village and Tirta Mulya using quantitative and qualitative descriptive methods. While the data used is primary data and secondary data obtained from interviews, questionnaires and literature from the village. The analytical tools used in this study are models of effectiveness, average difference testing and SWOT analysis. With the ultimate goal of wanting to get the results of the evaluation of the successful use of the Village Fund. The results showed that judged to be successful in the management of village funds, this was shown with an effectiveness rate reaching 100 percent (very effective). Furthermore, the use of Village Funds also has an impact on improving public services and health services but has not had an impact on improving the community economy.